E.M. Tareev: the importance of scientific heritage for the development of Russian internal medicine (on the 130th anniversary of his birth) - Sergey V. Moiseev; Lidia V. Lysenko; Sergei V. Guliaev; Svetlana Yu. Milovanova; Ludmila Yu. Milovanova (Терапевтический архив, 2025)
The article is dedicated to the memory of the outstanding Russian internist and scientist, academician of the Russian Academy of Medical Sciences – E.M. Tareev, who had a huge influence on the development of Russian medicine. The life and professional path of the scientist, his most significant scientific achievements in various areas of internal pathology, marked by high state awards and prestigious national prizes, are presented. The basic principles of the scientific school of E.M. Tareev are also presented, including his statements on the importance of maintaining at the present stage a broad general therapeutic approach to solving complex integrated tasks of health care.